Spectral and Photophysical Studies on Cruciform Oligothiophenes in Solution and the Solid State - Pina, J. (2006)
The photophysical and spectroscopic properties of a new class of oligothiophene derivatives, designated as cruciform oligomers, have been investigated in solution (room and low temperature) and in the solid state (as thin films in Zeonex matrixes). The study comprises absorption, emission, and triplet−triplet absorption spectra, together with quantitative measurements of quantum yields (fluorescence, intersystem crossing, internal conversion, and singlet oxygen formation) and lifetimes. The overall data allow the determination of the rate constants for all decay processes. From these, several conclusions are drawn. First, in solution, the main deactivation channels for the compounds are the radiationless processes: S1 S0 internal conversion and S1 T1 intersystem crossing. Second, in general, in the solid state, the fluorescence quantum yields decrease relative to solution. A comparison is made with the analogous linear α-oligothiophenes, revealing a lower fluorescence quantum efficiency and, in contrast to the normal oligothiophenes, that internal conversion is an important channel for the deactivation of the singlet excited state. Replacement of thiophene by 1,4-phenylene units in the longer-sized cruciform oligomer increases the fluorescence efficiency. The highly efficient generation of singlet oxygen through energy transfer from the triplet state (SΔ ≈ 1) provides support for the measured intersystem crossing quantum yields and suggests that reaction with this may be an important pathway to consider for degradation of devices produced with these compounds.